Pembangunan Hukum Ekonomi di Indonesia (Dalam Perspektif Alih Teknologi ) - Idris, Zulherman; Apriani, Desi; Rachman, Miftahur; Erlina, Erlina (UIR Law Review, 2019)
The existence of foreign capital which can be called the owner of the technology is very much needed. However, this great need and hope is not accompanied by a perfect clear legal basis, in fact specifically regarding technology transfer it is only contained and part of the law on foreign capital investment and patent provisions, whereas in reality the legal actions that occur cannot only be accommodated by the provisions foreign investment law and patents only, but also other aspects. This research is normative legal research which examines primary legal materials and other secondary data. From the results of the study, it was concluded that there are no specific regulations for technology transfer in Indonesia. In practice, it is only accommodated by licensing provisions, articles 9-13 of the Foreign Investment Law, and the Patent Law. Even these regulations are not yet representative and comprehensive so they cannot accommodate problems that arise in rapidly developing business practices. In connection with technology transfer regulations that do not yet have a specific code of conduct, this deficiency needs to be addressed relatively quickly so that there is certainty and legal protection for the parties involved in it, because so far the existing regulations have not been able to comprehensively accommodate legal problems. which arises mainly in relation to technology transfer which occurs through direct investment in the form of capital goods, except through licensing of technology.